The effect of living alone on the costs and benefits of surgery amongst older people. (February 2016) - Turner, Alex J.; Nikolova, Silviya; Sutton, Matt
Abstract: Older people who live alone are a growing, high-cost group for health and social services. The literature on how living alone affects health and the costs and benefits of healthcare has focused on crude measures of health and utilisation and gives little consideration to other cost determinants and aspects of patient experience. We study the effect of living alone at each stage along an entire treatment pathway using a large dataset which provides information on pre-treatment experience, treatment benefits and costs of surgery for 105, 843 patients receiving elective hip and knee replacements in England in 2009 and 2010. We find that patients who live alone are healthier prior to treatment and experience the same gains from treatment. However, living alone is associated with a 9.2% longer length of in-hospital stay and increased probabilities of readmission and discharge to expensive destinations. These increase the costs per patient by £179.88 (3.12%) and amount to an additional £4.9 million per annum. A lack of post-discharge support for those living alone is likely to be a key driver of these additional costs. Highlights: We study 105, 843 patients receiving elective hip and knee replacements in England. We follow patients along an entire treatment pathway. Patients living alone are healthier before treatment and have the same health gains. Living alone leads to longer stays, readmissions and costly discharge destinations. Costs per patient are increased by £180 (3.12%).